Is a State Bank a Useful Economic Development Tool in the United States? - Robert S. Chirinko (Center for Economic Studies and ifo Institute (CESifo), 2022)
The possibility of creating a state bank has received much recent attention in the United States. In 2021, six states introduced legislation to create a state bank; in 2019, similar legislation was enacted in California for municipal banks. This paper develops a framework to evaluate state banking, reviews prior experiences with state banking and related alternatives to traditional private banking and identifies five questions determining the advisability of creating a state bank. The overall goal is to shed some light on whether a state bank can be a useful tool to further state economic development and the welfare of state residents.
Keywords: G21; G28; H70; 330; state bank; public bank; credit allocation; economic development